Preferensi bekicot Achatina fulica Bowitch., (Pulmonata : Achatinadea) terhadap beberapa jenis tanaman sebagai pakan di daerah Manokwari - Dwi Irianti Handayani; Alexander Yaku; Yacob Bodang; Adelin Elsina Tanati; Sutiharni (Fakultas Pertanian Universitas Papua, 2019)
Preference is a form of statement that expresses feelings of preferring one thing over another. This study aimed to determine the preferences of snails (Achatina fulica) to several types of plants in the area of Manokwari. The method used in this research were descriptive method and field observation. Observations in the field were carried out by inventory of snails from the six plants, namely gedi, banana, papaya, sweet potato, cassava, and mustard greens, while data collection in the yard was carried out with an olfactometer to see the interest of snails in several types of plants. The results showed that snails liked the gedi plant the most while the least preferred was cassava.